Alternative splicing of Arabidopsis G6PD5 recruits NADPH-producing OPPP reactions to the endoplasmic reticulum - Linnenbrügger, Loreen; Doering, Lennart; Lansing, Hannes; Fischer, Kerstin; Eirich, Jürgen; Finkemeier, Iris; von Schaewen, Antje (Frontiers in Plant Science, 2022)
Glucose-6-phosphate dehydrogenase is the rate-limiting enzyme of the oxidative pentose-phosphate pathway (OPPP). The OPPP mainly provides NADPH and sugar-phosphate building blocks for anabolic pathways and is present in all eukaryotes. In plant cells, the irreversible part of the OPPP is found in several compartments. Among the isoforms catalyzing the first OPPP step in Arabidopsis, G6PD1 to G6PD4 target plastids (with G6PD1 being also directed to peroxisomes), whereas G6PD5 and G6PD6 operate in the cytosol. We noticed that alternative splice forms G6PD5.4 and G6PD5.5 encode N-terminally extended proteoforms. Compared to G6PD5.1, RT-PCR signals differed and fluorescent reporter fusions expressed in Arabidopsis protoplasts accumulated in distinct intracellular sites. Co-expression with organelle-specific markers revealed that the G6PD5.4 and G6PD5.5 proteoforms label different subdomains of the endoplasmic reticulum (ER), and analysis of C-terminal roGFP fusions showed that their catalytic domains face the cytosol. In g6pd5-1 g6pd6-2 mutant protoplasts lacking cytosolic G6PDH activity, the ER-bound proteoforms were both active, and thus able to form homomers. Among the Arabidopsis 6-phosphogluconolactonases (catalyzing the second OPPP step), we noticed that isoform PGL2 carries a C-terminal CaaX motif that may be prenylated for membrane attachment. Reporter-PGL2 fusions co-localized with G6PD5.4 in ER subdomains, which was abolished by Cys-to-Ser exchange in the 256CSIL motif. Among the Arabidopsis 6-phosphogluconate dehydrogenases (catalyzing the third OPPP step) S-acylated peptides were detected for all three isoforms in a recent palmitoylome, with dual cytosolic/peroxisomal PGD2 displaying three sites. Co-expression of GFP-PGD2 diminished crowding of OFP-G6PD5.4 at the ER, independent of PGL2’s presence. Upon pull-down of GFP-G6PD5.4, unlabeled PGD2 and PGL2 were enriched, but also enzymes that depend on NADPH provision at the ER, indicative of physical interaction with the OPPP enzymes. When membrane-bound G6PD5.5 and 5.4 variants were co-expressed with KCR1 (ketoacyl-CoA reductase, involved in fatty acid elongation), ATR1 (NADPH:cytochrome-P450 oxidoreductase), or pulled C4H/CYP73A5 (cinnamate 4-hydroxylase) as indirectly (via ATR) NADPH-dependent cyto¬chrome P450 enzyme, co-localization in ER subdomains was observed. Thus, alternative splicing of G6PD5 can direct the NADPH producing OPPP reactions to the cytosolic face of the ER, where they may operate as membrane-bound metabolon to support several important biosynthetic pathways of plant cells.